Inovasi Bridal Bouquet dari Bahan Manik dengan Teknik Pelintir - Yolanda Nastasya Sari Dewi; Nurulisma Saputri (Jurnal Riset Rumpun Seni, Desain dan Media, 2026)
The Bridal Bouquet is one of the essential accessories in weddings to complement the bride’s appearance. Fresh flowers tend to wither quickly, while synthetic flowers are considered less artistic. Therefore, the researcher created a product innovation: a Round Bridal Bouquet made of beads using the twisting technique. This study aims to describe the production process and determine public acceptance of the product. The research used the Research and Development (R&D) method consisting of nine stages. Data collection techniques included observation, documentation, literature study, and questionnaires with a descriptive qualitative approach. The production process was carried out systematically, starting from identifying potential and problems, drafting, product validation by five expert validators, product revision, trials, and distribution of questionnaires to 35 respondents. The results showed that the product innovation was well received by the public. The researcher suggests that this product can be further developed not only in round shape, but also in various other bouquet styles. Additionally, using lighter materials than beads is recommended for better comfort.